Desenvolvimento e avaliação de um mecanismo adaptável em dosador pneumático para individualização de sementes de arroz - Carpes, Dauto Pivetta (2019)
The objective of this research was to develop and evaluate a design composed of metering disc and scraper/excluder mechanism for its use in a picking doser with pneumatic aid, already existing in the agricultural market, to perform the individualization of rice seeds. The evaluations were conducted in the Agricultural Machinery Research and Development laboratory, linked to the Federal University of Santa Maria. A randomized block experimental design with bifactorial arrangement in 3x9 bands was used in four replications, totaling one hundred and eight experimental units. Factor A is composed of different conceptions of the developed doser, in three levels; factor D consists of seeding densities, tangential velocity of the metering discs and different levels of negative pressure, in nine levels. For the accomplishment of the tests in laboratory condition, the standards ABNT (1994), NBR (1987), ISO 7256/1 (1984) and ABNT 9743 (1987) were observed. The evaluation of the physical damage of the seeds showed that the mechanism labeled as disc 1 provided the lowest indexes, maintaining a high percentage of integrity. Regarding the evaluation of the conceptions, it was observed that the mechanisms presented different behaviors according to the variation of the negative pressure level and the tangential speed of the metering disc in order to obtain a larger number of seeds per meter. When increasing the diameter of the orifice of the metering disc, along with the negative pressure level, it increased the percentage of multiple spacings, however, for disc 3, which has the largest diameter, this rise caused an increase in the index of faulty spacing and mechanic damaging. Disc 1 presented the lowest damaging index and the best results for the variable acceptable spacings, with no significant difference among the employed negative pressures, obtaining averages of 42.00; 43.57 and 43.50 for the densities of 20 and 30 seeds per meter, respectively.